Analisis Kasus Pembatalan Klausula Arbitrase BANI oleh Pengadilan Negeri Jakarta Selatan (Studi Putusan Pengadilan Negeri Jakarta Selatan Nomor: 529/Pdt.G.ARB/2018/PN.Jkt.Sel) - Khikmah, Nurul; Khasabah, Karimatul (TAWAZUN: Journal of Sharia Economic Law, 2022)
In accordance with Law Number 30 of 1999 concerning Arbitration and Dispute Resolution, that dispute resolution at an arbitration institution is based on a written agreement from the parties to the dispute. The existence of an arbitration clause in the agreement brings legal consequences related to the absolute power of arbitration dispute resolution. This type of research is normative juridical legal research with a statutory approach. The data sources used are secondary data sources which consist of three legal materials, namely primary, secondary and tertiary. The analysis was carried out using an inductive descriptive technique. The results of this study indicate that efforts to annul arbitration can be submitted to the court provided that there are limitative conditions that must be fulfilled according to the alleged elements contained in Article 70 of Law Number 30 of 1999.